2005
DOI: 10.1097/01.tp.0000183750.22675.be
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Functions Improve with Decrease in Asymmetric Dimethylarginine (ADMA) Levels after Renal Transplantation

Abstract: The results indicate that ADMA is associated with FMD in CKD both before and after kidney transplantation. Endothelial functions improve at the very beginning of the posttransplantation period with accompanying reduction in ADMA and hsCRP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 36 publications
8
53
0
1
Order By: Relevance
“…ADMA, an endogenous inhibitor of NOS, is synthesized by the action of protein arginine methyl transferase on arginine residues of nuclear proteins. ADMA is released following proteolysis, and most of the freely circulating ADMA is metabolized by dimethylarginine dimethylaminohydrolase, which occurs mostly in the liver (29) but can also occur in other organs such as the kidney (46). Data from this model study have previously been described and shown to have renal dysfunction and changes in vascular dynamics as part of the developing multiple organ dysfunction syndrome (50).…”
Section: Discussionmentioning
confidence: 92%
“…ADMA, an endogenous inhibitor of NOS, is synthesized by the action of protein arginine methyl transferase on arginine residues of nuclear proteins. ADMA is released following proteolysis, and most of the freely circulating ADMA is metabolized by dimethylarginine dimethylaminohydrolase, which occurs mostly in the liver (29) but can also occur in other organs such as the kidney (46). Data from this model study have previously been described and shown to have renal dysfunction and changes in vascular dynamics as part of the developing multiple organ dysfunction syndrome (50).…”
Section: Discussionmentioning
confidence: 92%
“…As expected, blood urea nitrogen decreased signifi cantly after kidney transplantation. On the other hand, no signifi cant In general, plasma levels of some biomarkers indicating uremia or infl ammation decrease in patients with endstage renal disease (ESRD) after kidney transplantation ( 26,27 ). However, it is not known whether CYP3A activity recovers with improvement in renal function after kidney transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, 81% of patients experienced an improvement in central arterial pressure waveform after HD, and a reduction in ADMA level was present in 87% of patients. It was recently shown that renal transplantation also reduces ADMA levels and improves endothelial function and that these parameters correlate [25]. …”
Section: Discussionmentioning
confidence: 99%